PERBEDAAN KECEMASAN PADA IBU BERSALIN DENGAN PERSALINAN NORMAL DAN SECTIO CAESAREA: PERBEDAAN KECEMASAN PADA IBU BERSALIN DENGAN PERSALINAN NORMAL DAN SECTIO CAESAREA - Nuzula, Firdausi; Kasiati, K.; Maharrani, Titi (WELL BEING, 2021)
Background: Due to the painful nature of childbirth and its maternal and neonatal complications, the woman needs support in this phase of their life. The anxiety felt by women before caesarean delivery caused psychological problems, the increased of surgical pain therefore increased the need for pain relief, and prolong hospitalization. This study aimed to investigate the difference of anxiety in intrapartum mothers with normal and sectio caesarea. Subjects and Method: A cross sectional study was conducted at Haji hospital, Surabaya, East Java, Indonesia. A sample of 34 intrapartum mothers was selected by consecutive sampling. The dependent variable was anxiety. The independent variables were normal and section cesarea birth delivery. The data were collected by questionnaire and analyzed by independent t test. Results: There was no difference of anxiety in intrapartum mothers with normal birth delivery (Mean= 56.82; SD= 15.02) and mother those with section cesarea (Mean= 58.19; SD= 12.02). Conclusion: There is no difference of anxiety in intrapartum mothers with normal birth delivery and mother those with section cesarea.